Notes on Neoperla sinensis Chu, 1928 and Neoperla anjiensis Yang & Yang, 1998, with descriptions of new species of Neoperla from China (Plecoptera: Perlidae) - Huo, Qingbo; Du, Yuzhou; Zhu, Binqing; Yu, Lei (Zootaxa, 2021)
The identity of Neoperla sinensis Chu, 1928 is confirmed in this paper. Two new species of Neoperla, N. huangshana Huo, Du & Zhu, sp. nov. and N. pangi Huo, Du & Zhu, sp. nov. are proposed from Anhui Province, southeast China, closely related to N. sinensis. Neoperla anjiensis Yang & Yang, 1998 is newly recorded in Anhui Province.